Locating the Global in the Local: Ethnographic Fieldnotes on Citizenship Education Praxis in Elite School Classrooms in Lahore, Pakistan - Muhammad, Dr. Yaar; Qureshi, Dr. Naima; Rauf, Dr. Arjumand (ACADEMIA International Journal for Social Sciences, 2025)
This classroom ethnography study identifies the dialectical relationship between global citizenship education models and localised pedagogies in three English-medium elite schools in Lahore, Pakistan. This research used ethnographic fieldnotes as the main source of data to investigate the ways in which concepts of global citizenship are put to practice, negotiated, and recontextualised in everyday classroom interactions. This study questions the tension between universalist global citizenship education (GCE) discourses propagated by the global curriculum system and the local realities of Pakistani classrooms, where national identity, Islamic ideals, and social stratifications are used to inform citizenship education. Classroom observations recorded approximately 80 hours of teacher-student interactions and pedagogy strategies, curricular content, and the micro-politics of citizenship identity formation in the fieldnotes. Results indicate that elite schools serve as institutions of the process of "glocalization" in which teachers plan to mediate between the global skills required by international curriculum, and the local levels of sociocultural expectations. The paper shows that citizenship praxis in these classrooms both reinforces elite privilege and provides possibilities of critical involvement in transnational issues. Such an ethnographic narrative can lead to the understanding of global educational agendas being translated, opposed, and changed in postcolonial contexts to demonstrate the complex strata of global-local citizenship identities between the educational elite in Pakistan.